MODEL OF PROFESSIONAL QUALITIES FORMATION IN THE PROCESS OF PROFESSIONAL TRAINING OF FUTURE MANAGER IN THE CONTEXT OF GENDER FEATURES - Chemerinskaya, D. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article presents an model of professional qualities formation in the process of professional training of a manager at a university with in the context of gender features. The article reveals the target, methodological, organizational, informative, effective blocks of the model. It is noted that part of the methodological component is the laws built on the principles described. The final result is presented in the form of the formation of managerial qualities in a gender-sensitive environment.
Keywords: gender-sensitive environment, curriculum, model, the formation of professional qualities, vocational training